Estimates of soil nutrient limitation on the CO2 fertilization effect for tropical vegetation. (1st September 2022) - Fleischer, Katrin; Terrer, César
Abstract : The CO2 fertilization effect in tropical forests is a key factor for the global land carbon sink. We show that the normalized CO2 effect on tropical vegetation carbon was c. 70% lower in seedling CO2 experiments without nutrient fertilizers and c. 50% and 70% lower in models that consider nitrogen and phosphorus cycles, based on two model ensembles. The inadequate representation or lack of nutrient cycles in Earth System models likely leads to overestimating future tropical carbon gains.